(untitled) (Journal of Hama University, 2024)
This research about reforms which sultan Mahmoud II has made inside the ottomans army, during his rule time trying to reform and replace the ottomans military institution, after the appearance of feebleness and decay inside it . This research aims to know reforms and adjustments that sultan Mahmoud II has made in military institution which has weakened so it has focused on has found necessary resources and needs to improve army and continuing by finding out new economic systems , Mahmoud II hasn’t started reform until he’s overcomed the janissary army which was the first obstacle against reform , cause it refused the new reforms severely . so Mahmoud II has formed new military forces and started to train and arm these forces in modern European style. The research has showed military schooling so forming training these forces in modern manners need to build modern education system, so the sultan has directed to reform ottoman military education .A reform has been doing in European way so ottoman Education had ought to be as European Education in both side technical and ideology content , New military school have been built and military missions have been send to Europe, research has showed situation of ottoman marine and how Mahmoud II has developed it, He has considered that marine reform, is complementary part of military reform ,so that he has revived an old marine school , created new ones and send marine expedition to some European countries